PENGARUH MOTIVASI DAN SARANA PRASARANA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA DI SMP BHAKTI PERTIWI PROBOLINGGO - Asmoyo, M. Disin (Jurnal Manajerial Bisnis, 2023)
This research aims to 1) find out the description of Motivation, Infrastructure, Job Satisfaction and Teacher Performance at SMP Bhakti Pertiwi Probolinggo; 2) analyze the effect of Motivation on Teacher Job Satisfaction; 3) analyze the impact of Facilities and Infrastructure on Teacher Job Satisfaction; 4) analyze the effect of Job Satisfaction on Teacher Performance; 5) analyze the direct influence of Motivation on Teacher Performance; 6) analyze the direct impact of Infrastructure on Teacher Performance; 7) analyze the indirect effect of Motivation on Teacher Performance; 8) analyze the indirect effect of Infrastructure on Teacher Performance. The type of research is explanatory with a quantitative method approach. Research location at SMP Bhakti Pertiwi Probolinggo. The sample is all Bhakti pertiwi SMP teachers namely 32 people using the saturated sampling method. The data collection method used in this research: is questionnaire and documentation method. Data processing method using IBM SPSS 22 analysis. The results of the research: Motivation has a direct or indirect effect on the job satisfaction and performance of teachers; Infrastructural facilities have a direct impact on Job Satisfaction and indirectly on Teacher Performance. Job satisfaction has a direct impact on teacher.